6x-(2x-7)=23

Simple and best practice solution for 6x-(2x-7)=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(2x-7)=23 equation:


Simplifying
6x + -1(2x + -7) = 23
Reorder the terms:
6x + -1(-7 + 2x) = 23
6x + (-7 * -1 + 2x * -1) = 23
6x + (7 + -2x) = 23
Reorder the terms:
7 + 6x + -2x = 23
Combine like terms: 6x + -2x = 4x
7 + 4x = 23
Solving
7 + 4x = 23
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + 4x = 23 + -7
Combine like terms: 7 + -7 = 0
0 + 4x = 23 + -7
4x = 23 + -7
Combine like terms: 23 + -7 = 16
4x = 16
Divide each side by '4'.
x = 4
Simplifying
x = 4

You can always share this solution

See similar equations:

| 1+5p+8=-11 | | 0.75(16x-24)=32 | | 35=5*n+2 | | 24-6h=6(4-h) | | .3a+.7=.5a-.1 | | 5(4x-13)= | | 4a-23=5-10a | | -13x-20=-11+60 | | 4y-16-8y=-4 | | 2x(2+4x)=18 | | 2y-8=-.5(3-5y) | | 20=4*x+3 | | 2x-6=3x+5 | | 2a/3+6=35 | | -2y+1=-3(2y+5) | | -4w=-12 | | 0=64t-16t^2 | | 7-2n=n-143 | | 2a+6=35 | | 8(x+2)=64 | | 12-6w=10-5w | | 4(3x+5)=10x+2 | | 9x-55+3x+35=180 | | 2(x+10)-6=2 | | 25x-1=9 | | -8m+1-m=12+7 | | 40=64t-16t^2 | | 2y+3+2y=y+6 | | 0=x^4+8x^3-9x^2 | | (3x+7+3x+7)+(4x-2+4x-2)= | | 0.5= | | 2.5+1.3=1.3h-2.3 | | 0.75(8+2y)=3 | | -7(x+2)-43=6-14 | | 12x-3(-4x+3)+5=13 | | -5w+2=15w-10 | | 2x-2=24 | | 6x+152+3x+91=180 | | 3x+10+x-30=180 | | x^2-3x-150=0 | | .07x+.08(4x+32000)=46630 | | 4w*3w+2w=24 | | 25x+6-27x=4-6 | | 2(2b-4)=10-2b | | 11x+9=13(11-x) | | 10y=12-4x | | .5x+10=20 | | (36x^2)-120x=-70 | | -31y=434 | | 14=7x-4+2x | | 5+2(x+8)=-3 | | 19.72+6.5z=4.8z | | 32x+3=40x-3 | | 4x-16=24 | | 15-4x=x-5 | | (8x-10+8x-10)+(6x+6x)= | | 250+16x=210+18x | | 15d-8=2d | | (36x^2)-120=-70 | | 5h+2g=23 | | -14.8+0.2s=-16.4s+19.85+18.7s | | 8-5(2a+3)= | | y=-9-2x | | 8z-1=3z+6 | | |3-2b|=-7 |


Related pages


what is the square root of 1089what is 3y2n3112x squared1973 in roman numeralsfraction solver with stepswhat is the square root of 3922x-4y 4square root of 2809what is 1996 in roman numerals9cxhow to graph y 2x 4prime factorization 542pirstep by step equation solverdifferentiate sin squared xmultiples of elevendivisors of 755.75 as a fractionwhat is 0.375 as a fractionwhat is the prime factorization of 10012x-3 squareddifferentiate cos2xderivative ln 2xx2 4x 12what is the lcm of 6 7 9prime factorization of 588graph the equation y 3xderivative of e to the x squaredlcm of 144prime factorization of 9320 off 49.99ln secxdivide by fraction calculator821000prime factorization of 4402x 5y 122n31sin50simplify sin2x2x 4y 1060-1.52x-5y 0how to change fractions to decimalsac15cpvrntprime factors of 40573-100write percent as a fraction calculatorsimplify the square root of 147cosine 2piderivative of ln costconvert percent to fraction calculatormultiples of 252cosx cosy13337xsen 2x14 x 24prime factorization of 79213x 5x 32408-4x 5y 10 graphfraction to decimal solverfind the prime factorization of 1051vyderivative of lnx 2500-1750.3 as a decimal25kg to lbfactor tree for 72factor 2x2 5x 12graph 4x y 8555333360-250adding and subtracting fractions with variables calculatorlcm of 4 and 3gcf of 54 and 63what is the prime factorization of 123